Injuries in German national short-track speed skating athletes - Ziegler, J.; Beck, H.; Bell, R. L.; Matzner, D.; Tian, X.; Zwingenberger, S. (JSAMS Plus, 2025)
Objectives Short-Track Speed Skating (STSS) is a high-intensity ice sport characterized by fast-paced races and proximity among athletes, which inherently poses a risk for falls and injuries. This paper presents a comprehensive analysis of orthopedic-traumatological injuries in German national STSS athletes with comparisons to previous studies.